AN INVESTIGATION ON ACADEMICS’ EMOTIONAL LABOUR LEVELS - BALCI, Velittin; ERDEVECİLER, Övünç and ALTINSOY, Ülkü (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2019)
This study aimed to evaluate the level of the academics’ emotional labor, which has become an economic value and which can be the predecessor or successor of many organizational behavior variables, and to evaluate what kind of relatively superior features it contains in terms of superficial, deep role-playing and natural emotion. In this study; 398 academicians from 4 universities in Hacettepe, Gazi, Ankara and Bilkent University participated in Ankara. The reason for collecting data from academicians is that they are among the occupational groups that are most expected for emotional labor. In the study, we used quantitative research model, and to gather data in addition to personnel information form, we used the Turkish version of Diefendorff et all’ s emotional labor scale. The data analyzed with SPSS 21 package program using frequency, percentage, independent samples t-test, and one-way ANOVA. According to the analysis results, when we examined the demographic data of the participants, we found that 49.7% were female, and 50.3% were male. When the age groups were examined, it was found that the average was 40.63. In the findings of the study conducted to determine the emotional labor levels of academic staff, significant differences were found only in the ’superficial role-playing’ sub-dimension of the t-test results according to gender, while no significant difference was found in the other sub-dimensions. There was a statistically significant difference in the overall scale (p = .0200; p <.05). According to ANOVA results, there were no significant differences in overall and in the sub-dimensions of the scale. Considering that the concept of emotional labor is essential for employees who are mostly in face-to-face communication, more meaningful and generalizable results can be achieved by applying this scale in different occupational groups other than academics.